Microstructural models for diffusion MRI in breast cancer and surrounding stroma: an ex vivo study. (21st December 2016) - Bailey, Colleen; Siow, Bernard; Panagiotaki, Eleftheria; Hipwell, John H.; Mertzanidou, Thomy; Owen, Julie; Gazinska, Patrycja; Pinder, Sarah E.; Alexander, Daniel C.; Hawkes, David J.
Abstract : The diffusion signal in breast tissue has primarily been modelled using apparent diffusion coefficient (ADC), intravoxel incoherent motion (IVIM) and diffusion tensor (DT) models, which may be too simplistic to describe the underlying tissue microstructure. Formalin‐fixed breast cancer samples were scanned using a wide range of gradient strengths, durations, separations and orientations. A variety of one‐ and two‐compartment models were tested to determine which best described the data. Models with restricted diffusion components and anisotropy were selected in most cancerous regions and there were no regions in which conventional ADC or DT models were selected. Maps of ADC generally related to cellularity on histology, but maps of parameters from more complex models suggest that both overall cell volume fraction and individual cell size can contribute to the diffusion signal, affecting the specificity of ADC to the tissue microstructure. The areas of coherence in diffusion anisotropy images were small, approximately 1 mm, but the orientation corresponded to stromal orientation patterns on histology. Abstract : Ex vivo human breast cancer samples were scanned using a rich diffusion protocol and fitted to a variety of models. Two‐compartment models with restriction and anisotropy best explained the data in most regions. Regions with anisotropic diffusion signal corresponded to regions of aligned collagen on histology, but with coherence over only 1–2 mm.